ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP PADA MATERI BENTUK ALJABAR DI SMP IT NURUL HUDA BATUJAYA - Silfina Ihza Hayati; Rina Marlina (IKIP Siliwangi, 2021)
Describing students' abilities in understanding mathematical concepts in class VII SMP IT Nurul Huda Batujaya in learning mathematics in algebraic forms is the aim of the study. Using a qualitative descriptive method and then data analysis, namely, data reduction, data presentation and drawing conclusions. The research instrument used tests and interviews. The type of test is a description test. Judging from the results of the student's ability test on algebraic form material in understanding concepts, it is classified as low. As well as the results of interviews with students who find difficulties including: difficulty in distinguishing elements that exist in algebraic form, difficulties in substituting equations, and difficulties in arithmetic operations in algebraic forms.